2009
DOI: 10.1371/journal.pone.0005262
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Thresholds Regulate Inflammation through the NF-κB Pathway: Experiments and Modeling

Abstract: BackgroundDuring normal physical activities cartilage experiences dynamic compressive forces that are essential to maintain cartilage integrity. However, at non-physiologic levels these signals can induce inflammation and initiate cartilage destruction. Here, by examining the pro-inflammatory signaling networks, we developed a mathematical model to show the magnitude-dependent regulation of chondrocytic responses by compressive forces.Methodology/Principal FindingsChondrocytic cells grown in 3-D scaffolds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 16 publications
7
91
0
6
Order By: Relevance
“…In fact, previous gene expression studies of cells subjected to large mechanical loads have reported regulation of stress and inflammatory genes. 15,35,36 In comparison, there were no signs of upregulation of inflammatory or stressrelated genes in the present study, supporting the suggestion of an appropriate level of strain being utilized. Our study also showed a markedly lower total number of changes in gene expression in response to a mechanical loading.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, previous gene expression studies of cells subjected to large mechanical loads have reported regulation of stress and inflammatory genes. 15,35,36 In comparison, there were no signs of upregulation of inflammatory or stressrelated genes in the present study, supporting the suggestion of an appropriate level of strain being utilized. Our study also showed a markedly lower total number of changes in gene expression in response to a mechanical loading.…”
Section: Discussionsupporting
confidence: 82%
“…[33][34][35] To determine the functional significance of such induction of NOS, the effect of L-NAME, an inhibitor of NOS, was assessed in this model of an AVF. Such inhibition led to an exaggeration of the histological changes observed in the venous limb along with the up-regulation of pro-inflammatory genes such as MCP-1 and CINC-1, the latter representing the rat homologue of human IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…This response includes early activation of pro-inflammatory transcription factors, NF-B and AP-1, transcription factors known to be activated in endothelial cells by shear stress. [33][34][35]43,44 It is tempting to speculate that activation of these transcription factors represents a maladaptive response to hemodynamic stress in the venous segment of an AVF since this response sets the stage for ensuing inflammation and neointimal hyperplasia. The significance of hemodynamic stress in this model is underscored by the fact that systemic hypertension, as imposed by two different models, exacerbated venous neointimal hyperplasia in the AVF; the adverse effects of systemic hypertension on the longevity of AVFs merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling events activated in chondrocytes and other resident cells are common to both mechanotransduction and cytokine stimulation [ 20 ]. A large number of studies have addressed interleukin-1 (IL-1) as a major infl ammatory cytokine that drives the progression of the disease (see for review [ 21 , 22 ]).…”
Section: Role Of Infl Ammation In Cartilage Damage In Ptoamentioning
confidence: 99%
“…The fi ndings that mechanical stimuli modulate NF-κB signaling [ 20 ] provide an explanation for why NF-κB-related gene signatures may be upregulated in mouse models of PTOA in the absence of overt signs of infl ammation such as synovitis and immune cell infi ltration. Such profi ling studies have revealed that infl ammatory signatures are present before the appearance of overt OA and, in some models, are associated with increased numbers of activated T-and B-lymphocytes in the spleens of the mice destined to develop OA [ 50 ].…”
Section: Lessons From Mouse Modelsmentioning
confidence: 99%